Religious controversy and Scottish society, c.1679-1714 - Raffe, Alasdair J. N. (The University of Edinburgh, 2007)
This thesis analyses religious controversy in late seventeenth - and early eighteenth-century Scotland, examining both the arguments of the educated elites and those of ordinary people. Defining religious controversy as arguments between members of rival religious parties, the thesis concentrates on disputes between presbyterians and episcopalians, and within presbyterianism. In the main, these arguments did not focus on Church government, but embraced a broad range of issues, including allegations of ‘persecution’ (discussed in chapter two), ‘fanaticism’ and ‘enthusiasm’ (chapter three) and the reputations of rival clergy (chapter four). Incidents of crowd violence, the subject of chapter five, provoked controversy, and also promoted the objectives of the religious parties. Chapter six illustrates the significance of debates over the National Covenant and the Solemn League and Covenant, before and after the revolution of 1688-90. Chapter seven then discusses the arguments that gave rise to presbyterian separatism in the years after 1690. As chapter eight explains, the union of 1707 proved highly contentious for presbyterians, and led to a series of political blows to the presbyterian Church. Chapter nine surveys the role in religious controversy of concerns over English theology, new philosophy and atheism. Finally, chapter ten concludes by examining the consequences of controversy for Scottish society. As well as printed pamphlets, satirical verses, sermons and memoirs by elite authors, the thesis draws on the petitions, diaries and correspondence of ordinary people, their testimony to church courts, and evidence of their involvement in crowd violence and separatist worship. Participation in controversy by ordinary men and women was widespread, and was deliberately manipulated by elite presbyterians and episcopalians, who sought to demonstrate the popularity of their parties. By 1714, the position of the established Church and the status of its clergy had deteriorated, and religious pluralism had become a permanent feature of Scottish society.
Keywords: religion; society; National Covenant; Solemn League and Covenant